2021
DOI: 10.3390/pathogens10030300
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Induces IFN-β Production via a CARMA3-Independent Mechanism

Abstract: Type I interferon (IFN) induction is a critical component of innate immune response to viral and bacterial infection, including S. aureus, but whether it activates the signaling in macrophages and the regulation mechanisms is less well understood. Here we show that S. aureus infection promoted the IFN-β mRNA expression and stimulator of IFN genes (STING)/TANK-binding kinase 1 (TBK1)/ interferon regulatory factor 3 (IRF3)-dependent production of IFN-β. Infection with S. aureus induced caspase recruitment domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Our data are in line with other studies showing a STING dependent IFN-β production in RAW 264.7 cells or mouse BMDMs upon infection with clinically relevant SA strains [23,31]. STING activation was only observed for living SA and disappeared when bacteria were heat-killed indicating that the stimulus had to be actively produced by the bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are in line with other studies showing a STING dependent IFN-β production in RAW 264.7 cells or mouse BMDMs upon infection with clinically relevant SA strains [23,31]. STING activation was only observed for living SA and disappeared when bacteria were heat-killed indicating that the stimulus had to be actively produced by the bacteria.…”
Section: Discussionsupporting
confidence: 92%
“…However, STING deficiency did not worsen pulmonary inflammation during the early stage of infection [88]. Another study that implicated cGAS/STING signalling in S. aureus infection showed that S. aureus infection promoted IFN-β mRNA expression and TBK1/IRF3-dependent production of IFN-β in murine macrophages [40]. Production of IFN-β has been reported to be protective against S. aureus infection, as IFN-β is required to turn on downstream genes important for local inflammatory responses [89].…”
Section: Cgas-sting Pathwaymentioning
confidence: 99%
“…CDNs bind to the endoplasmic reticulum (ER)-localised STING, which promotes STING dimerization and translocation from the ER to golgi compartments [36,37] where STING recruits and activates TBK1 and nuclear translocation of the transcription factor IRF3) and to a lesser extent, NF-κB) [38], leading to the production of type 1 IFNs and many other inflammatory cytokines. Type I IFN induction is a critical component of innate immune response to several bacterial pathogens including S. aureus [40].…”
Section: Cgas-sting Pathwaymentioning
confidence: 99%
“…During the early stage of S. aureus infection, the Toll-like receptor (TLR) and cGAS-STING pathways are both activated by live S. aureus but exhibit opposite roles in the host immune response to S. aureus. TLR signaling restricts infection, while the cGAS-STING pathway enhances bacterial growth ( 83 , 84 ). The transcription and expression of IFN-I are well-known to be induced by phosphorylation of IRF3.…”
Section: Intracellular Gram-positive Bacteriamentioning
confidence: 99%